Inggris: Inggris - Nasrulloh Nasrulloh; Ahmad Muhammad Sa’dul Kholqi (UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
Women in religion and culture-historical study have a journey of oppression, adversity and, discrimination. Women have always been used as objects of pleasure and victims of lust for men. Many interpretations of religious texts discriminate against women. Many religious figures look down on women through their interpretation of the texts of Al-Qur'an and Sunnah. One of the interpretations is the opinion of the majority of community leaders about the prohibition of women as imams of congregational prayer. This research aims to determine the views of the community from Muhammadiyah, NU, HTI, and Malang Raya Mosque Management regarding the meaning of the hadith of women's delegation as imam (congregational prayer leader) from a social construction perspective. This research is included in the category of qualitative research using the sociological construction theory approach, and the science of hadith criticism. This researcher used a new model in the realm of hadith research, named living hadith. Data collection methods in this research were in-depth interviews and documentation. The selection of informants used a purposive sampling technique. The analytical technique used in this research was the Huberman and Miles interactive model, namely; data reduction, data display, and conclusion. The understanding of activists of religious organizations Muhammadiyah, NU, HTI, and Mosque Management regarding the hadith negation of women being imams of prayer can be classified into two models of understanding. There are textual and contextualist-hermeneutical. Public understanding of the hadith regarding the delegation of women to become imam comes from hadith, opinions of classical scholars, contemporary books, and also comes from the results of intuitive meanings that lead to conservative and progressive.